Malbec variety grape seeds. A waste product from the wine industry containing fatty acids, resveratrol, anthocyanins, and antioxidant compounds - Gonzales-Condori, Elvis Gilmar; Quispe-Mamani, Alfredo Enrique; Jove-Román, Janeth Rocio; Pacheco-Torreblanca, Georgia Janette (LACCEI, 2024)
Waste from the wine industry is produced in large quantities worldwide. This waste is grape pomace, composed of stems, skins, and seeds. This study aimed to determine fatty acids, resveratrol, anthocyanins, and antioxidant capacity in Malbec grape seeds. First, the oil was extracted from the previously pulverized grape seeds and then the fatty acids were quantified by gas chromatography and resveratrol by spectrophotometry. The results showed that the oil presented a concentration of palmitoleic, stearic, oleic, and linoleic acids of 13.54, 7.06, 32.43, and 51.74 %, respectively, and a resveratrol concentration of 2.89 ± 0.15 mg/kg. Subsequently, the extract of defatted seeds was obtained using ethanol: H2O: HCl and 70 % ethanol, finding a concentration of total anthocyanins of 258.05 ± 5.89 and 121.55 ± 2.42 mg C3G/ 100 g, respectively, and an antioxidant capacity of 15.12 ± 0.12 mmol TE/L and 13.75 ± 0.17 mmol TE/L, respectively. The present study is of crucial importance for developing research in companies dedicated to the production of wine to valorize the components found and take advantage of these wastes economically since their composition can be of pharmaceutical and biotechnological interest.